Conhecendo o vitiligo: uma cartilha para exemplificar o vitiligo para o público infantil - Cavalcante Júnior, Silvando Carlos (2024)
Vitiligo is a non-contagious skin condition common to many people, however, studies that deal with it in an informative way are rarely carried out. The present work consists of the study and development of a prototype of a booklet aimed at children, addressing and exemplifying vitiligo through illustrations, didactic texts based on Tim Brown's design methodology, Design Thinking (2009) and editing proposed by Lins (2003) analyzed by Panizza (2004), moving through the stages of understanding, analysis, development and finalization of the prototype.